2020
DOI: 10.1038/s41386-020-0741-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-term nicotine deprivation alters dorsal anterior cingulate glutamate concentration and concomitant cingulate-cortical functional connectivity

Abstract: Most cigarette smokers who wish to quit too often relapse within the first few days of abstinence, primarily due to the aversive aspects of the nicotine withdrawal syndrome (NWS), which remains poorly understood. Considerable research has suggested that the dorsal anterior cingulate cortex (dACC) plays a key role in nicotine dependence, with its functional connections between other brain regions altered as a function of trait addiction and state withdrawal. The flow of information between dACC and fronto-stria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 127 publications
(130 reference statements)
0
13
0
Order By: Relevance
“…Moreover, previous studies on the changing phases of CD have mostly focused on quantitative assessments of the GI tract or the gut microbiome, other than potential brain abnormalities; most of the researches were conducted based on mono-modality imaging that only covers sMRI, fMRI or MRS, a multi-modality research is infrequent though it may better reflects the underlying neurophysiological effects of specific brain areas (Becker et al, 2021;Cococcioni et al, 2021). Abulseoud et al (2020) combined the use of rs-fMRI with MRS to investigate functional activity in the human brain to investigate the effects of short-term nicotine deprivation, considering that compared with using task-induced BOLD signal changes, the time needed for resting-state detections of BOLD signals is more similar to that needed for acquiring the relatively static Glu in MRS (Abulseoud et al, 2020). Zhang et al (2016) found the altered amplitude of low frequency fluctuation (ALFF) values in medial prefrontal cortex (mPFC) correlated positively with regional levels of glutamate in female patients with depression.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies on the changing phases of CD have mostly focused on quantitative assessments of the GI tract or the gut microbiome, other than potential brain abnormalities; most of the researches were conducted based on mono-modality imaging that only covers sMRI, fMRI or MRS, a multi-modality research is infrequent though it may better reflects the underlying neurophysiological effects of specific brain areas (Becker et al, 2021;Cococcioni et al, 2021). Abulseoud et al (2020) combined the use of rs-fMRI with MRS to investigate functional activity in the human brain to investigate the effects of short-term nicotine deprivation, considering that compared with using task-induced BOLD signal changes, the time needed for resting-state detections of BOLD signals is more similar to that needed for acquiring the relatively static Glu in MRS (Abulseoud et al, 2020). Zhang et al (2016) found the altered amplitude of low frequency fluctuation (ALFF) values in medial prefrontal cortex (mPFC) correlated positively with regional levels of glutamate in female patients with depression.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the role of nicotine withdrawal in the delirium cannot be ruled out (Mayer et al 2001 ). We have recently shown that acute nicotine withdrawal causes disruption in anterior cingulate glutamatergic homeostasis and functional connectivity (Abulseoud et al 2020 ), and both factors contribute to delirium pathology (Wilson et al 2020 ; Oh et al 2019 ). Similarly, the possibility of alcohol withdrawal in the non-alcohol cohorts cannot be excluded, since we do not have data on alcohol consumption prior to presentation.…”
Section: Discussionmentioning
confidence: 99%
“…CEF treatment (200 mg/kg/day) twice daily for 4 days reduced reinstatement to nicotine in mice using the CPP paradigm ( Alajaji et al, 2013 ). We have shown that short-term nicotine abstinence is associated with reduced glutamate concentration in the dACC in humans ( Abulseoud et al, 2020 ), and that CEF decreased nicotine withdrawal manifestations in rats ( Alajaji et al, 2013 ) and attenuated nicotine preference using the CPP paradigm ( Philogene-Khalid et al, 2017 ). To the best of our knowledge, there are only few studies that report the efficacy of CEF pretreatment in reducing nicotine-seeking behavior, preference in CPP, and withdrawal manifestations.…”
Section: Regulation Of Hyperglutamatergic State With Ceftriaxonementioning
confidence: 99%